Influence of TRPV1 on diabetes-induced alterations in thermal pain sensitivity - Pauza Mary E; Khardori Romesh; Peng Siying; Yu Shuang-Quan; Pabbidi Reddy M; Premkumar Louis S (SAGE Publishing, 2008)
Abstract A common complication associated with diabetes is painful or painless diabetic peripheral neuropathy (DPN). The mechanisms and determinants responsible for these peripheral neuropathies are poorly understood. Using both streptozotocin (STZ)-induced and transgene-mediated murine models of type 1 diabetes (T1D), we demonstrate that Transient Receptor Potential Vanilloid 1 (TRPV1) expression varies with the neuropathic phenotype. We have found that both STZ- and transgene-mediated T1D are associated with two distinct phases of thermal pain sensitivity that parallel changes in TRPV1 as determined by paw withdrawal latency (PWL). An early phase of hyperalgesia and a late phase of hypoalgesia are evident. TRPV1-mediated whole cell currents are larger and smaller in dorsal root ganglion (DRG) neurons collected from hyperalgesic and hypoalgesic mice. Resiniferatoxin (RTX) binding, a measure of TRPV1 expression is increased and decreased in DRG and paw skin of hyperalgesic and hypoalgesic mice, respectively. Immunohistochemical labeling of spinal cord lamina I and II, dorsal root ganglion (DRG), and paw skin from hyperalgesic and hypoalgesic mice reveal increased and decreased TRPV1 expression, respectively. A role for TRPV1 in thermal DPN is further suggested by the failure of STZ treatment to influence thermal nociception in TRPV1 deficient mice. These findings demonstrate that altered TRPV1 expression and function contribute to diabetes-induced changes in thermal perception.